Framtidsvisioner och drömmen om evigt liv: Transhumanism, kropp och teknologi - Farstad, Britt Johanne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
In this article I discuss transhumanism and ideas about “enhanced humans” and “incipient posthumans” as it is described in popular science. In our time we don’t find utopist ideas about futuristic technology in science fiction literature, but they prosper in popular science. Futuristic dreams, written by researchers who describe what they wish to accomplish with their work, above all they want to live long and forever. They want to get rid of their biological bodies altogether and live as information patterns on large extremely powerful computer networks. They want to eventually become ageless creatures with vastly improved intellectual, emotional, and moral capacities. Human nature as we currently know it is valued as “an early draft of a work-in-progress”. They want to live long enough to benefit from advanced life-extension procedures, participate in direct human-machine interfaces, including implants of sensory enhancements, memory expansion, health monitoring, and communication devices, among others. In other words: they don’t want to die.